2021
DOI: 10.51248/.v41i4.121
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on effect of platelet rich plasma Vs conventional dressing in healing rate of chronic diabetic ulcers

Abstract: Introduction and Aim: This study has been undertaken to evaluate efficacy of platelet rich plasma (PRP) dressing that is recently introduced with conventional dressing. We have tried to compare PRP dressing with conventional normal dressing in healing the wound.   Materials and Methods: We conducted this study in 120 patients of chronic non healing diabetic foot ulcers who were treated over the period of three years. Number of cases (60 each) were studied for efficacy of applying autologous platelet rich plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Only two studies, Goda20 and Somani and Rai21, had L-PRF gel as an intervention, the remaining five had PRP gel. Among the seven studies, two were conducted in India,21 22 two in Egypt,20 23 and the remaining studies were conducted in the USA,24 China25 and Turkey,26 respectively. Four studies were conducted in patients with diabetic ulcers,22–25 two in patients with venous leg ulcers20 21 and one in patients with pressure ulcers 26…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two studies, Goda20 and Somani and Rai21, had L-PRF gel as an intervention, the remaining five had PRP gel. Among the seven studies, two were conducted in India,21 22 two in Egypt,20 23 and the remaining studies were conducted in the USA,24 China25 and Turkey,26 respectively. Four studies were conducted in patients with diabetic ulcers,22–25 two in patients with venous leg ulcers20 21 and one in patients with pressure ulcers 26…”
Section: Resultsmentioning
confidence: 99%
“…Only five studies reported the proportion of ulcers completely healed, four studies reported time to complete healing and five studies reported the rate of healing per unit of time. Five studies reported mean age in years at baseline in terms of mean and SD21–24 26 The mean age (SD) ranged from 39.3 (8.2) to 68.3 (6.4) years. The sample size ranged between 9 and 60 subjects in both intervention and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations